Public Sector Integrity in Addressing the Corruption in Public Organizations in Indonesia - Leo B. Barus (Social Sciences and Humanity Studies, 2022)
Public officers in certain public organizations in Indonesia are experiencing with crisis of public sector integrity considering that the handling of corruption cases carried out by the Corruption Eradication Commission in 2014-2022 has reached 1,351 cases, committed by unscrupulous members of the certain members of the people's representative assembly, Ministries/Institutions, state/regional owned enterprises, Commission, Provincial Government, and Regency/City Government. It is concluded that the addressing of corruption in public organizations in Indonesia can be done by strengthening the integrity of the public sector. Strengthening the integrity of the public sector which can legitimize public organizations is carried out by upholding the ethical culture and building the appropriate integrity management system at the organizational level.